Penerapan (Tabel Pejumlahan Pintar) TAPEntar Terhadap Pembukuan Keuangan Usaha Tape Di Desa Pakem Bondowoso - Wapa, Andi; Wijaksono, Agus; Yusuf, Thorieq Moh.; w, a; y, t (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Negeri Banyuwangi, 2024)
This community service aims to provide an understanding of simple bookkeeping for TAPE business actors in Pakem village, Pakem sub-district, Bondowoso district. Entrepreneurship is something that is very hotly discussed, starting from creating types of business such as permits from the relevant government to setting the concept which must be more measurable so that the business being developed becomes more useful and produces positive results. The method used is based on the criteria for achieving maximum understanding and outcomes regarding bookkeeping. so that business actors can do it well. Based on understanding through counseling activities and workshops regarding bookkeeping using the TAPEntar type, the pre-questionnaire results were 93.2% in the category of never having attended training, while the post-questionnaire results at the end could increase drastically to 98.2% who already understood bookkeeping using TAPEntar.